THE EFFECT OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) AND BUSINESS STRATEGY ON BUSINESS PERFORMANCE IN SMALL AND MEDIUM BUSINESSES - Siti Maemunah (Universitas Trisakti, 2017)
This study aims to analyze the influence of information and communication technology (ICT) and business strategies on business performance in small and medium enterprises. This research is quantitative, descriptive survey that uses SEM methodology. Data collection is carried out in small and medium enterprises that have a workforce of 5-19 people for small businesses and 20-99 people for medium-sized businesses. Second, small and medium enterprises have assets of 50 million-500 million rupiah for small businesses and more than 500 million to 5 billion rupiah for medium-sized businesses. The number of samples is 250. The results of the study were processed using LISREL 8.80, in the model and hypothesis testing. The results of this study prove that small and medium enterprises are more open in responding to the rapid development in the field of information and communication technology to build competitive advantages against competitors.